Constructing an emergency preparedness evaluation index system for public use during major emerging infectious disease outbreaks: a Delphi study - Wei Wei; Yubei Liu; Na Zhou; Min Tian; Longsheng Xie; Roger Watson; Fengling Dai; Yanhua Chen; Weili Hu (BMC Public Health, 2023)
Abstract Background The major emerging infectious diseases (MEIDs) have occurred frequently and become increasingly serious in the world. Sufficient personal emergency preparedness is critical for the general people in efficiently responding to and recovering from MEIDs. Nevertheless, few specific indicators are available for assessing the individual emergency preparedness of the general public during these periods. Therefore, the aim of this study was to construct an index system for comprehensively evaluating the personal emergency preparedness of the public regarding MEIDs. Methods Based on the global national-level emergency preparedness index framework and a literature review, a preliminary index system was constructed. From June 2022 to September 2022, a panel of 20 experts from nine provinces and municipalities across multiple research areas participated in this Delphi study. They rated the importance of pre-defined indicators using a five-point Likert scale and provided their qualitative comments. According to the feedback of each round of experts, the indicators of the evaluation index system were revised. Results After two rounds of expert consultation the evaluation index system reached a consensus, containing five first-level indicators, cooperating with prevention and control work, improving emergency response capacity, securing supplies and equipment, preparing economic resources, maintaining physical and mental health with affiliated 20 s-level indicators and 53 third-level indicators. The expert authority coefficient of consultation was 0.88 and 0.90. The Kendall’s coefficient of concordance of expert consultations was 0.294 and 0.322, respectively. The differences were statistically significant (P < 0.05). Conclusion A valid, reliable and scientific evaluation index system was established. This personal emergency preparedness index system, as a precursor form, will further lay the foundation for the formation of an assessment instrument. At the same time, it could provide a reference for future education and training of emergency preparedness for the general public.